Role of EFL teachers' beliefs in speaking practice: The case of a Mexican university. (December 2020) - Garcia-Ponce, Edgar Emmanuell; Tagg, Caroline
Abstract: In English as a foreign language (EFL) classrooms, learners' communicative opportunities are maximised when they practise speaking. However, in the context of Mexican teacher education, teachers have been seen to adapt speaking practice in response to contextual factors in a way which limits learners' speaking competence development. Drawing on evidence which shows that teacher beliefs strongly influence classroom practices, the study firstly measures and describes interactional features of three EFL teachers and learners during speaking practice in this Latin American context. It then explores the teachers' beliefs about speaking practice in interviews. In combining these data, it aims to examine the role of their beliefs in speaking practice. The findings suggest that the teachers' decisions and teaching practices may be shaped by their attempts to reconcile communicative principles with their continuing beliefs in the importance of traditional grammar teaching and their perceptions regarding practical constraints (class time and size). In particular, these belief systems may encourage display questions over referential questions, speaking activities focused on grammar or vocabulary, and teacher dominance of talk. These findings provide an opportunity to understand the potential role of beliefs in shaping speaking practice in EFL contexts in Mexico.